New Directing Groups for Metal-Catalyzed Asymmetric Carbon–Carbon Bond-Forming Processes: Stereoconvergent Alkyl–Alkyl Suzuki Cross-Couplings of Unactivated Electrophiles - Wilsily, Ashraf (2012)
The ability of two common protected forms of amines (carbamates and sulfonamides) to serve as directing groups in nickel-catalyzed Suzuki reactions has been exploited in the development of catalytic asymmetric methods for cross-coupling unactivated alkyl electrophiles. Racemic secondary bromides and chlorides undergo carbon–carbon bond formation in a stereoconvergent process in good ee at room temperature in the presence of a commercially available nickel complex and chiral ligand. Structure-enantioselectivity studies designed to elucidate the site of binding to nickel (the oxygen of the carbamate and of the sulfonamide) led to the discovery that sulfones also serve as useful directing groups for asymmetric Suzuki cross-couplings of racemic alkyl halides. To the best of our knowledge, this investigation provides the first examples of the use of sulfonamides or sulfones as effective directing groups in metal-catalyzed asymmetric carbon–carbon bond-forming reactions. A mechanistic study established that transmetalation occurs with retention of stereochemistry and that the resulting nickel–carbon bond does not undergo homolysis in subsequent stages of the catalytic cycle.